Long Covid – The illness narratives. (October 2021) - Rushforth, Alex; Ladds, Emma; Wieringa, Sietse; Taylor, Sharon; Husain, Laiba; Greenhalgh, Trisha
Abstract: Callard and Perego depict long Covid as the first illness to be defined by patients who came together on social media. Responding to their call to address why patients were so effective in making long Covid visible and igniting action to improve its care, we use narrative inquiry – a field of research that investigates the place and power of stories and storytelling. We analyse a large dataset of narrative interviews and focus groups with 114 people with long Covid (45 of whom were healthcare professionals) from the United Kingdom, drawing on socio-narratology (Frank), therapeutic emplotment (Mattingly) and polyphonia (Bakhtin). We describe how storytelling devices including chronology, metaphor, characterisation, suspense and imagination were used to create persuasive accounts of a strange and frightening new condition that was beset with setbacks and overlooked or dismissed by health professionals. The most unique feature of long Covid narratives (in most but not all cases) was the absence, for various pandemic-related reasons, of a professional witness to them. Instead of sharing their narratives in therapeutic dialogue with their own clinician, people struggled with a fragmented inner monologue before finding an empathetic audience and other resonant narratives in the online community. Individually, the stories seemed to make little sense. Collectively, they provided a rich description of the diverse manifestations of a grave new illness, a shared account of rejection by the healthcare system, and a powerful call for action to fix the broken story. Evolving from individual narrative postings to collective narrative drama, long Covid communities challenged the prevailing model of Covid-19 as a short-lived respiratory illness which invariably delivers a classic triad of symptoms; undertook and published peer-reviewed research to substantiate its diverse and protracted manifestations; and gained positions as experts by experience on guideline development groups and policy taskforces. Highlights: Long Covid is a patient-defined illness which gained legitimacy in online communities. We analysed long Covid narratives using socio-narratology. Narrators used literary devices to make sense of illness and persuade their audiences. A unique feature of many narratives was absence of a professional therapeutic witness. Storytelling may be a key means by which online communities achieve collective action.